The Determinants of SME Credit Rationing in Morocco. Case of SMEs in the Casablanca Settat Region - BOUTFSSI, Adil; QUAMAR, Tarik (Theoretical and Practical Research in Economic Fields; Vol 15 No 4 (2024): TPREF Volume XV, Issue 4(32), Winter 2024, 2024)
In this article, we are concerned with a central element of the Moroccan economy, namely small and medium-sized enterprises (SMEs), which often find themselves in a situation where alternative sources of financing are not easily accessible, including bank financing. Indeed, Moroccan SMEs are closely dependent on banking institutions to obtain the financial support necessary for their projects. However, these businesses frequently face the phenomenon of credit rationing, necessitating improved access to credit. In this research work, we have contributed to the study of this phenomenon, focusing specifically on the Casablanca Settat region. Our research revolves around two essential objectives. Firstly, we aimed to evaluate the impact of credit rationing on SMEs in this region. Next, we focused on empirically identifying the determinants of this phenomenon. To achieve these objectives, we selected a target population of 218 SMEs from the Casablanca Settat region. Our initial statistical tests revealed that SMEs in the Casablanca-Settat region are facing both total credit rationing and partial credit rationing. Subsequently, the results obtained from multinomial logistic regression tests reveal that the SME's sector of activity, age, reputation, legal status, size, gender of its manager, age, education, nature of the relationship with the bank, and professional experience all play an important role in explaining this phenomenon.